Erythromycin induced Torsade de Pointes in a Methadone maintenance patient:case report - Robson, Noor Zurani; Habil, M.H. (ASEAN Federation of Psychiatry and Mental Health (AFPMH), 2010)
Objective: This case report highlights the risk of Torsade de Pointes (TdP), a life threatening cardiac arrhythmia in a heroin dependent patient receiving methadone substitution therapy who was prescribed erythromycin for upper respiratory tract infection. Method: We report a case of a 35-year-old Malay man on methadone maintenance treatment who developed TdP possibly due to drug interaction between methadone and erythromycin. Results: The patient reported feeling unwell, chest pain and feeling dizzy after consuming 2 doses of erythromycin. ECG monitoring showed prolonged rate-corrected QT interval leading to TdP. The patient was admitted to the ward where the cardiac arrhythmia ceased following methadone discontinuation. This cardiac arrhythmia was most likely due to drug interaction between methadone and erythromycin (an enzyme inhibitor) which led to an increase in methadone concentration and potentiated the adverse effects. Conclusion: As methadone is a beneficial treatment for heroin dependent patients, the risk of cardiac arrhythmia is of great concern. To avoid complications of drug interaction, patients on methadone therapy should be advised to seek medical assessment before taking other drugs. As TdP is life threatening, it is thus important that physicians and psychiatrists involved in the treatment of heroin dependent patients on methadone substitution therapy be made aware of this risk.